When ICT ensures pedagogical continuity in times of crisis : Case of Ibn Zohr University, Morocco - Samar CHAKHRATI (International Journal of Scientific Research and Innovative Studies, 2025)
The year 2020 was marked by the advent of the COVID-19 pandemic, whose impact on the entire world was unprecedented. The rapid spread of this virus has led to health, economic, and social crises on a global scale. Indeed, it is one of the greatest challenges we have faced since World War II. Information and Communication Technologies (ICT) have indeed brought significant changes in the field of university education, improving access to information, enabling distance learning, facilitating collaboration and communication, and offering innovative tools for learning and assessment. These changes have not only enriched the educational experience but have also opened new perspectives for education on an international scale. Keyword : Covid-19, ICT, higher education, usage, representations. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at <a href="https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/447" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/410&source=gmail&ust=1758927666749000&usg=AOvVaw03AJMbViD5ahcBHILB0530">https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/447